Methodology for calculating financial result for the owner of the infrastructure from increasing carrying capacity of the direction during operation in cars with increased capacity - O. F. Miroshnichenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
In accordance with the draft Long-Term Development Program of the JSC “Russian Railways” until 2025, the main driver of growth in freight turnover in this perspective will be a further increase in the transportation of hard coal. It will occur both due to the growth of coal production in Kuzbass and due to the development of new coal deposits. For the period up to 2025, the increase in coal loading by 4 – 5 % per year is predicted on rail transport. Under these conditions, it becomes necessary to increase the capacity of the transport complex, especially the carrying and transport capacities of the Eastern Operation Area.The article presents the methodology for calculating economic effect of increasing the carrying capacity of the site during operation in cars with increased axle load. The scope of this methodology is speciﬁc areas (sections), taking into account their technical, operational and economic parameters.Variant calculations were made, the results of which showed that an increase in the carrying capacity of a section with an increase in the mass of a train formed from cars with increased axle loads does not always give a signiﬁcant positive effect in terms of value for the infrastructure owner. Positive effect of the increase in carrying capacity in the form of additional profits from the additionally used traffic volume in the evaluated variant can be taken into account in the following cases:- operation of large-capacity cars on freight-intensive sections where there is a lack of carrying capacity in the billing period, i. e. the carrying capacity of the section is less than its required value;- exceeding the freight charge for the additional volume of freight carriage incurred transportation costs, i. e. if the tariff compensates for at least the dependent part of the cost of additional volume transportation.Positive economic effect of the increase in carrying capacity in the form of increased money ﬂow is achieved if the proﬁt from the additional trafﬁc volume in the direction exceeds the additional costs associated with changing the technology for servicing the traction arms while promoting high-weight trains formed from cars with increased axle loads. In other words, if there is no increase in the value of the indicator of mileage (in section-km) per unit of transport work, and the unit cost of maintaining one section with a new technology for servicing traction arms.